'Caring schools' – a solution for addressing challenging behaviour in schools? - Weeks, F. H. (Koers, 2008)
Media reports suggest that challenging behaviour is no longer the exception to the rule in South African schools. Furthermore, such problem behaviour is increasingly violent in nature, thus constituting a particular cause for concern. In this article the concept of “caring schools” is explored as a means of addressing learners’ challenging behaviour. A research study was undertaken at eight South African primary schools. The conclusions drawn from this research were verified by the correlative research findings of other researchers, as ascertained from the literature study. A key element of this research was the identification of attributes associated with caring schools and the impact thereof on learners’ behaviour patterns. From the findings of this research study it is concluded that caring schools represent a possible solution for dealing with challenging behaviour in South African schools.